Hyperbaric oxygen in combination with exosomes: a new strategy to promote tissue repair - Zhang, Shengchao; Zhou, Jiaqi; Liu, Jia; Li, Tong; Liu, Yong; Gao, Yuling (Frontiers in Bioengineering and Biotechnology, 2025)
Tissue repair is an essential mechanism for restoring damage caused by disease and maintaining life in organisms. Hyperbaric oxygen therapy, as a non-invasive physical treatment, has been utilized to address various tissue damage conditions. Exosomes are nanoscale vesicles released into the extracellular environment by animal cells. Their structure comprises a phospholipid bilayer membrane and includes specific functional active components, such as nucleic acids, lipids, and proteins. It can precisely modulate the behavior of target cells, restore the balance of the microenvironment, and stimulate endogenous regeneration and repair mechanisms, representing a novel tool in regenerative medicine. Evidence indicates that hyperbaric oxygen in conjunction with exosomes can markedly enhance tissue healing. Currently, there is a paucity of research about the synergistic application of the two, however they are intrinsically linked to the principles of tissue repair. Therefore, this article systematically explains the application and mechanism of hyperbaric oxygen and exosomes therapy on tissue repair, the interaction between the two, and the combined application of the two, and analyzes the safety and transformation obstacles of the combined treatment strategy, in order to provide new ideas for future combined research and clinical application.